Design and Analysis of Multiband Bloom Shaped Patch Antenna for IoT Applications - et.al, R Ramasamy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Microstrip Bloom shaped patch antenna is proposed for Internet of Things (IoT) application. This antenna operates at multiband frequencies between 1.6 GHz to 2.45 GHz. The Bloom shaped antenna provides multiband response that examined in HFSS Software. In this proposed antenna design, FR4 substrate material is used because it is easily available and low cost. The proposed antenna structure simulated and analyzed in different experimental results including return loss measurement, Voltage Standing Wave Ratio measurement, radiation pattern measurement and gain measurement. This proposed Multiband Microstrip Bloom shaped patch antenna provides better experimental results in all the parameters